Comparison of Spatial Distribution Patterns of Dung-Feeding Scarabs (Coleoptera: Scarabaeidae, Geotrupidae) in Wooded and Open Pastureland in the Mediterranean “Dehesa” Area of the Iberian Peninsula - GALANTE, E; GARCIA-ROMAN, M; BARRERA, I; GALINDO, P (Environmental Entomology, 1991)
The seasonal and spatial distributions of dung-feeding scarabs in an open pastureland and in wooded (holm oak) pastureland in a typical Mediterranean area of the western part of the Iberian Peninsula (Salamanca) were compared. Six pitfall traps baited with bovine dung were placed in each habitat according to a model by J. P. Lumaret. Only beetles in the families Scarabaeidae and Geotrupidae were studied because they are the most important agents in the elimination of cattle dung from the soil surface. Weekly trapping for 1 yr produced 6,909 specimens. Of the 18 species found, the largest beetles and biomass were concentrated mainly in the wooded habitat, especially in the summer. This constitutes a problem for dung removal because large amounts of dung remain in open pasturelands, possibly resulting in the impoverishment of such areas.
Keywords: dung beetles; Geotrupidae; Insecta; Scarabaeidae